Diaphragmatic hernia repair using a rectus abdominis muscle pedicle flap in three dogs - Chantawong, P.; Komin, K.; Banlunara, W.; Kalpravidh, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective: To report the clinical use of a pedicle flap from the rectus abdominis muscle to repair extensive diaphragmatic tears in dogs with diaphragmatic hernia.Materials and methods: Three dogs with a combination of radial and circumferential diaphragmatic tears were studied. The circumferential tear was repaired by suturing the wound edge with the edge at the abdominal wall. A pedicle flap of the rectus abdominis muscle was used for repairing the radial tear. The dogs were examined radiographically for lung and diaphragm appearance and evidence of reherniation at 10 days, and at one, two, and four months after surgery, and fluoroscopically for paradoxical motion of the diaphragm at one and four months.Results: The rectus abdominis muscle pedicle flap was successfully used in all three dogs. The animals recovered uneventfully without evidence of reherniation during the four follow-up months. Fluoroscopic examination revealed no paradoxical motion of the diaphragm.Clinical significance: A rectus abdominis muscle pedicle flap can be used for repairing large diaphragmatic defects in dogs.
Keywords: Herniorrhaphy; Diaphragmatic hernia; Rectus abdominis muscle; pedicle graft; dogs